1995
DOI: 10.1007/bfb0025890
|View full text |Cite
|
Sign up to set email alerts
|

SIMPLE performance results in ZPL

Abstract: Abstract. This paper presents performance results for ZPL programs running on the Kendall Square Research KSR-2 and the Intel Paragon. Because ZPL is a data parallel language based on the Phase Abstractions programming model, these results complement earlier claims that the Phase Abstractions model can lead to portability across MIMD computers. The ZPL language and selected aspects of the compilation strategy are brie y described, and performance results are compared against hand-coded programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The first step towards achieving good parallel performance is to achieve good performance on a single node. Experiments on sequential computers have shown that ZPL is competitive-typically within a few percent-with languages such as C and Fortran [36,32,20]. Comparisons against hand-coded message passing programs [13,36] show similar success.…”
Section: Empirical Evidence Of Successmentioning
confidence: 99%
See 2 more Smart Citations
“…The first step towards achieving good parallel performance is to achieve good performance on a single node. Experiments on sequential computers have shown that ZPL is competitive-typically within a few percent-with languages such as C and Fortran [36,32,20]. Comparisons against hand-coded message passing programs [13,36] show similar success.…”
Section: Empirical Evidence Of Successmentioning
confidence: 99%
“…Experiments on sequential computers have shown that ZPL is competitive-typically within a few percent-with languages such as C and Fortran [36,32,20]. Comparisons against hand-coded message passing programs [13,36] show similar success. For example, Figure 5 shows that for 64 processors on the IBM SP-2, a ZPL implementation of the SIMPLE fluid dynamics benchmark [21] is about 16% slower than the same program written using C and MPI.…”
Section: Empirical Evidence Of Successmentioning
confidence: 99%
See 1 more Smart Citation
“…ZPL generally outperforms HPF and has proven to be competitive with hand-coded C and message passing [10,9]. Applications from a variety of disciplines have been written using ZPL [4,7,14], and the language was released for widespread use in July, 1997.…”
Section: Introduction To Zplmentioning
confidence: 99%